Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.seizure.2019.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic usefulness of arterial spin labeling in MR negative children with new onset seizures

Abstract: A B S T R A C TPurpose: Arterial spine labeling (ASL) magnetic resonance imaging (MRI) is the non-invasive measurement of cerebral blood flow that can localize the seizure focus in patients with epilepsy. The aim of this study was to identify its utility for localizing the seizure focus in children with no structural lesion on MRI. Methods: Forty-three consecutive children who underwent electroencephalography (EEG) and structural MRI, along with ASL for evaluation of newly developed seizures, were included. AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…The C2 class comprises voxels where patients had gray matter loss, decreased perfusion, hypometabolism, higher perfusion in ictal state compared to interictal state, decrease of barriers for water diffusion, and enhanced water diffusion. This is in accordance with previous findings: the GMV loss was shown especially in temporal‐lobe patients with HS (Bernhardt, Hong, Bernasconi, & Bernasconi, 2015); decreased perfusion was reported in children (Lee et al, 2019); the hypometabolism seen in PET and interictal/ictal‐specific perfusion assessed by SPECT are well‐known markers of epileptogenic tissue (Krsek et al, 2013; Rathore, Dickson, Teotonio, Ell, & Duncan, 2014); and microstructure abnormalities in epileptogenic tissue identified by diffusivity metrics were reported to be sensitive to FCD (Feindel, 2013; Winston et al, 2020). The C4 class is similar to that of C2.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The C2 class comprises voxels where patients had gray matter loss, decreased perfusion, hypometabolism, higher perfusion in ictal state compared to interictal state, decrease of barriers for water diffusion, and enhanced water diffusion. This is in accordance with previous findings: the GMV loss was shown especially in temporal‐lobe patients with HS (Bernhardt, Hong, Bernasconi, & Bernasconi, 2015); decreased perfusion was reported in children (Lee et al, 2019); the hypometabolism seen in PET and interictal/ictal‐specific perfusion assessed by SPECT are well‐known markers of epileptogenic tissue (Krsek et al, 2013; Rathore, Dickson, Teotonio, Ell, & Duncan, 2014); and microstructure abnormalities in epileptogenic tissue identified by diffusivity metrics were reported to be sensitive to FCD (Feindel, 2013; Winston et al, 2020). The C4 class is similar to that of C2.…”
Section: Discussionsupporting
confidence: 93%
“…We used arterial spin labeling (ASL), which quantifies cerebral blood flow (Boscolo Galazzo et al, 2015) and has a potential to reveal perfusion abnormalities in patients with focal seizures (Lee, Kwon, & Lee, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Pediatric patients with acute seizures and no abnormalities on structural MRI were studied with ASL and EEG. The study by Lee et al 23 showed concordance (kappa = 0.542) between ASL findings and clinical seizure focus. Therefore, ASL may have a role in evaluating epilepsy in the setting of normal structural MRI.…”
Section: Seizurementioning
confidence: 88%
“…ASL perfusion revealed areas of focal hyperperfusion that corresponded to the presumed seizure onset zone in newborns [34] and in children who presented with a first seizure and normal MRI [35 ▪ ]. Perfusion changes were detected in 58% of children (focal in 36 and generalized in seven patients) with an overlapping area between the TPMA and the suspected seizure onset zone in 76%.…”
Section: Peri-ictal Imagingmentioning
confidence: 99%